2013 Kansas Performance Tests With Soybean Varieties - Schapaugh, William T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
Soybean performance tests are conducted each year to provide information on the relative performance of new and established varieties and brands at several locations in Kansas. Contributors Main Station, Manhattan William T. Schapaugh, Jr., Professor (Senior Author) Jane Lingenfelser, Assistant Agronomist Nathan Keep, Research Assistant Hatice Aslan, Research Assistant Research Centers Patrick Evans, Colby Kelly Kusel, Columbus Monty Spangler, Garden City Josh Coltrain, Crawford County Extension Experiment Fields Eric Adee, Topeka Gary Cranmer, Hutchinson James Kimball, Ottawa Wendell Lilyhorn, Hutchinson Randall Nelson, Belleville and Scandia Cooperators Vernon Egbert, McCune Lance Rezac, Onaga Dale Roberds, Pittsburg Clayton Short, Assaria
Keywords: Soybeans; Seeds; Yields; Environmental factors; Kansas